Coaching psicopedagógico para la orientación vocacional a estudiantes de tercero de bachillerato en la Unidad Educativa Quevedo - Molina García, Domenica Michelle (2025)
The study aimed to provide vocational guidance to third-year high school students through the implementation of a strategy based on psychopedagogical coaching. It was identified that young people faced difficulties in vocational choice due to a lack of self- knowledge, social pressure, and limited information about academic and vocational options, which generated anxiety and insecurity in decision-making. To address this issue, a qualitative research approach was used, with a descriptive and non-experimental design. Surveys were conducted with 38 students third-year high school students from section "A,”, and an interview was carried out with a tutor from Unidad Educativa Quevedo. The results showed that a high percentage of students did not have sufficient information to choose a career and that vocational guidance within the institution was limited. Additionally, the influence of external factors, such as familial and social pressure, on vocational decision-making was evident. In response to these findings, a psychopedagogical coaching strategy was designed, including the application of vocational tests, self-knowledge workshops, and decision-making support sessions. The validation of the strategy by specialists and teachers confirmed its feasibility and applicability in the educational context. In conclusion, psychopedagogical coaching proved to be an effective tool for strengthening vocational guidance, as it promotes self-knowledge, reduces anxiety, and enhances confidence in vocational choice, thus contributing to the comprehensive development of students.